Interleukin and prostaglandin status of patients with shingles depending on the severity of the disease - O. M. Novytskyi; I. S. Haidash (Patologìâ)
Aim. The aim of the work is to study the interleukin and prostaglandin status of patients with shingles depending on the severity of the disease.